Transcervical resection of myoma (TCRM): Part I - Peng-Hui Wang; Szu-Ting Yang; Wen-Hsun Chang; Hung-Hsien Liu; Wen-Ling Lee (Taiwanese Journal of Obstetrics & Gynecology)
Uterine fibroids occur frequently in women during the reproductive age, and they are rarely associated with clinical meaning because of their benign characteristics and asymptomatic clinical presentation. Sometimes, uterine fibroids are symptomatic and associated with compression syndrome, infertility, chronic pelvic pain and heavy menstrual bleeding. All need further intervention and treatment. Medication is often preferred and frequently applied but symptom-control rate is varied, resulting the need of further active treatment. An effective but minimally invasive procedure such as surgery is sometimes used as back up strategy in the management of women with no response to medical treatment. Additionally, fertility-sparing or uterus-preservation is the main goal and becomes very popular in both physicians and patients. Conservative surgical treatment can be made according to myoma location. Simply, myoma is classified as submucosal, intramural and subserous types. However, to offer a practical standardized consensus for the description and categorization of myomas, the International Federation of Gynaecology & Obstetrics (FIGO) classification system from type 0 to type 8 is established, which is often used for guiding patient management and offering prognostic information, because submucosal myoma (FIGO type 0, 1, probable 2, and possible 3) is frequently associated with symptoms or signs, needing a further intervention. Transcervical resection of myoma (TCRM, also called as hysteroscopic myomectomy: HM) is the treatment of choice for submucosal myoma, and this increased trend is secondary to its nearly non-trauma in nature, even compared to other MIS, such as mini-laparotomy and laparoscopic or robotic approach. Although TCRM is becoming more and more popular in modern clinical practice, the risks and limitations of TCRM are often overlooked. In this review as part I, we will focus on the rationale, efficacy, complication, and limitation of using TCRM in the management of women with symptomatic uterine fibroids. Under the well-training and carefully performing TCRM, TCRM not only provides the less traumatic injury to the uterus, but also offers an effective and safe strategy in dealing with symptomatic submucosal myoma.